ANALISIS PENGARUH STRATEGI DIGITAL MARKETING, E-SERVICE QUALITY, SERTA PRODUCT QUALITY TERHADAP KEPUTUSAN PEMBELIAN USED CAR SHOWROOM WIDJAYA MOTOR PADA ENIGMA PANDEMI COVID - 19 - Ferdy Fachrul Widanta; Nurul Hilmiyah; Setiarini (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2023)
This study aims to determine the effect of digital marketing strategies, e-service quality, and product quality on purchasing decisions for Widjaya Motor's used car showroom during the Covid-19 pandemic enigma. The data collection method used a questionnaire with a sample size of 150 respondents. The object of this study were consumers from the Widjaya Motor showroom who had made purchases via the internet. The data analysis method used was descriptive quantitative analysis using the SPSS Statistics 24 application. The results in this study used the classical assumption test, multiple linear regression analysis, and hypothesis testing techniques. The results of the study show that digital marketing, e-service quality, and product quality have a significant positive effect on purchasing decisions, meaning that consumers have trusted the Widjaya Motor showroom as a showroom that excels in digital marketing, e-service quality, product quality. Researchers suggest for future research to add other variables.